INEQUALITY AND GROWTH IN TUNISIA: EMPIRICAL EVIDENCE ON THE ROLE OF MACROECONOMIC FACTORS - MBAZIA, Nadia (Theoretical and Practical Research in Economic Fields; Vol 8 No 2 (2017): TPREF, Volume VIII, Issue 2(16), Winter 2017DO - 10.14505/tpref.v8.2(16).08, 2017)
The purpose of this paper is to explore the relationships between income inequality, economic growth and the main macroeconomic factors in Tunisia. We investigate two effects:  the effect of inequality on growth, and particularly, the effect of growth on inequality. Also, attention has been focused on the role of the monetary policy, via introducing money supply as an independent variable, in affecting inequality and growth. Our empirical study is based on a series of annual data from 1975 to 2015 using the Dynamic Ordinary Least Squares (DOLS) method in order to estimate the cointegrating equations. The findings of the paper show that income inequality increase economic growth in Tunisia. Other factors having significant positive effect on economic growth include money supply and life expectancy at birth. However, inflation rate, primary education and unemployment have statistically significant and negative effect on economic growth. On the other hand, the results indicate that money supply, inflation rate, unemployment and savings are positively and significantly related to income inequality, whereas, life expectancy at birth and gross fixed capital formation decrease inequality in Tunisia. The policy implications of these results are discussed.